Levels of proprotein convertase subtilisin/kexin type 9 in patients with acute myocardial infarction - A. D. Gimadeeva; A. S. Galyavich; Z. M. Galeeva; L. V. Baleeva (Российский кардиологический журнал, 2020)
Aim. To study the levels of proprotein convertase subtilisin/kexin type 9 (PCSK9) in patients with acute myocardial infarction (MI).Material and methods. The study included 74 patients with acute MI. PCSK9 was determined by enzyme-linked immunosorbent assay.Results. The mean PCSK9 levels were 479,7±15,4 ng/ml. No significant correlation was found between PCSK9 and total cholesterol, low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), triglycerides. In the group of smokers, a significant inverse correlation was found between the levels of PCSK9 and HDL-C (-0,45; p=0,039). In the group of patients with body mass index <25 kg/m2, a significant inverse correlation of PCSK9 levels with total cholesterol (-0,45, p=0,008), HDL-C (-0,42; p=0,029) and LDL-C (-0,47; p=0,003) was found.Conclusion. In patients with MI, a correlation of PCSK9 levels with lipid profile was found in smokers, as well as in patients with a low body mass index.